Pengaruh Pengetahuan Pajak, Kualitas Pelayanan Samsat, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Semarang - Triyastuti Handayani; Maryono Maryono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Motor vehicle tax compliance is crucial for increasing regional tax revenue, which serves as a source of funding for development. However, compliance levels in Semarang City remain suboptimal and are influenced by several factors. This study aims to examine the influence of tax knowledge, the quality of service provided by SAMSAT (One-Stop Administration Services Office), and taxpayer awareness on compliance levels regarding motor vehicle tax obligations. A quantitative approach was employed, utilizing primary data collected via questionnaires from 100 motor vehicle taxpayers at the Semarang City SAMSAT, selected using the accidental sampling method. Data analysis was conducted using multiple linear regression in SPSS version 25, supported by statistical tests such as descriptive analysis, classical assumption tests, the coefficient of determination test, simultaneous testing (F-test), and partial testing (t-test). The results indicate that the level of tax knowledge has a significant negative impact on taxpayer awareness regarding the fulfillment of motor vehicle tax obligations. Conversely, SAMSAT service quality and taxpayer awareness have a positive and significant impact on compliance. These findings suggest that improving service quality and enhancing taxpayer awareness are more effective strategies for boosting compliance than merely increasing understanding of tax regulations.